THE FACT OF HEDGES IN OPRAH WINFREY TALK SHOW (NOBEL: Journal of Literature and Language Teaching, 2013)
The main purpose of this study is to identify and describe the types of hedges (in others study termed as taxonomy of hedges) as well as the pragmatic functions that the hedges/hedging expressions creating the implied meaning in Oprah Winfrey Talk Show. By following Evans‟ (2006) theory on the types of hedges/hedging expressions, this study found that Oprah Winfrey Talk Show contains 9 (nine) types of hedges/hedging expressions which are equally used by Oprah Winfrey toward her interlocutors.In terms of pragmatic functions of hedges/hedging expressions, it is found that most the hedges/hedging expressions are used for mitigating a criticism or request and softening a stance or opinion. This identification is following Simpsons‟ (2010) finding on her study about hedges in scientific discourse. In addition, the result of this study suggests that the use of hedges/hedging expressions (in the talk show) carries speaker and sentences implicature.The findings of this research also indicate that hedges/hedging expressions can be used to signal the sensitivity to other‟s feeling. This means that the use of hedges/hedging expressions may help to feel what others‟ feeling about, through the context of the conversation. As the result, even it is like common conversation but there are many politeness utterances considerably. Therefore, it is suggested that the study about the use of hedges/hedging expressions could be extended, strengthened and improved in the practical contexts to cover the attempts to help students develop their ability of speaking and competence in rearrange the topic into smooth and good communication. In a broader perspective, the use of hedges/hedging expressions could be developed, either through practical teaching in the classroom or through language researches.Key Words: hedges, pragmatic function of hedges, implicature.